An Intelligent Healthcare Box Based on IoT Technology - Liu, Xingchen (fi=Turun yliopisto|en=University of Turku|, 2017)
With the aging of the social population problem developing, the medical and nursing needs of the elderly are rising. Therefore, many Internet of Things (IoT) healthcare works came into being. They provide simple healthcare functions, but still have a variety of functional deficiencies. In order to meet the needs of household healthcare, this thesis designs an IoT intelligent healthcare box for family or other healthcare institutions. Based on the analysis of the defects of current works, a unique medicine classification and detection system is designed. It realizes the management and interaction with portable healthcare IoT devices. The system on cloud platform achieves the real-time monitoring and recording of healthcare information. Based on the functional analysis, this work can be divided into three sub-systems including the medication behavior detection and feedback, the portable device management and the cloud platform information integration. In the part of hardware design, this work uses the Central Processing Unit (CPU) module designed by our health IoT group as the control core of embedded gateway. This thesis uses Radio Frequency Identification (RFID) to achieve medicines classification and detection, and designs the integrated Bluetooth module to connect with portable devices. The software design with two aspects: embedded software design and cloud platform software design. The offline part realizes the data uploading and warning feedback. The online software achieves the data filtering and integrated information displaying. This system can be applied to many different household application scenarios. It is a great help to build a complete online healthcare records system.